The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s00148-011-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Political regimes and the family: how sex-role attitudes continue to differ in reunified Germany

Abstract: Political regimes, Gender-role attitudes, German reunification, J13, J16,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 13 publications
6
129
1
1
Order By: Relevance
“…Even though most men and women report that the family is more valuable than work and even there have been many changes in the household production allocation the last 50 years, the traditional gender roles persist. The study by Bauernschuster and Rainer (2010) explored and compared the gender role attitudes between Eastern and Western Germany and they found that these attitudes are less traditional in Eastern Germany because of the different political systems suggesting that the gender roles might diverge in the western world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though most men and women report that the family is more valuable than work and even there have been many changes in the household production allocation the last 50 years, the traditional gender roles persist. The study by Bauernschuster and Rainer (2010) explored and compared the gender role attitudes between Eastern and Western Germany and they found that these attitudes are less traditional in Eastern Germany because of the different political systems suggesting that the gender roles might diverge in the western world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marital behavior differs sharply between the two previously separate German states, as unmarried parenthood is very common in the East, where more than 60 % of children are born to unmarried mothers. In addition to a large EastWest gap in nuptiality patterns, eastern and western Germans differ sharply when it comes to women's employment patterns and attitudes towards maternal employment, and these differences have been found to persist even among the generation of eastern and western Germans who were born and raised after reunification (Bauernschuster / Rainer, 2012). This ongoing gap in family and fertility patterns suggests that women and men do not mechanically adjust their behavior to new constraints, but that attitudes have their own dynamics, and are resistant to change even under new economic and institutional conditions (Huinink et al, 2012).…”
Section: Motivation For Conducting the Studymentioning
confidence: 99%
“…The researchers explain their findings by an establishment of constant behavioral norms early in life. Bauernschuster and Rainer (2012) show a widening of the east-west gap in sex-role attitudes, for example regarding the statement whether it is important for a women to support her husband's career instead of her own. Heineck and Süssmuth (2010) find persistence of a lower level of social trust in East Germany.…”
Section: Introductionmentioning
confidence: 99%